AGRO-SYSTEM (AGS) AS A TOOL FOR ANALYSIS, TAKING INTO ACCOUNT SUSTAINABILITY - WATANABE, Kassia; ZYLBERSZTAJN, Decio (Revista Brasileira de Engenharia de Biossistemas, 2011)
The purpose of this article is to present agro-system (AGS) as a tool for analysis, considering sustainability. This tool can be applied in different system, such as agri-food, bio-diesel system and among others. The question for this article is: How can sustainability be analyzed in AGS? AGS analysis is important, since it can point improvements or even introduce new institutional arrangement (organization forms). However, an institutional arrangement might not be good enough when transplanted to other place and local institutions should be considered. For this reason, the AGS is analyzed within institutional environment that involves the "rules of game". Moreover, social and environment issues are concerned and are part of institutional arrangement and institutional environment as well.